Apple device management : a unified theory of managing Macs, iPads, iPhones, and Apple TVs - Edge, Charles S., Jr; Trouton, Rich (Apress, 2023)
Working effectively with Apple platforms at a corporate or business level includes not only infrastructure, but a mode of thinking that administrators have to adopt to find success. A mode of thinking that forces you to leave 30 years of IT dogma at the door. This book is a guide through how to integrate Apple products in your environment with a minimum of friction. Because the Apple ecosystem is not going away. You'll start by understanding where Apple, third-party software vendors, and the IT community is taking us. What is Mobile Device Management and how does it work under the hood. By understanding how MDM works, you will understand what needs to happen on your networks in order to allow for MDM, as well as the best way to give the least amount of access to the servers or services that's necessary. You'll then look at management agents that do not include MDM, as well as when you will need to use an agent as opposed to when to use other options. Once you can install a management solution, you can deploy profiles on a device or you can deploy profiles on Macs using scripts. With Apple Device Management as your guide, you'll customize and package software for deployment and lock down devices so they're completely secure. You'll also work on getting standard QA environments built out, so you can test more effectively with less effort. This thoroughly revised and expanded Second Edition provides new coverage and updates on daemons and agents, declarative management, Gatekeeper, script options, SSO tools, Azure/Apple Business Essentials integrations and much more.